2008
DOI: 10.1094/pdis-92-4-0519
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Pathogenicity of Lasiodiplodia theobromae and Diplodia seriata, the Causal Agents of Bot Canker Disease of Grapevines in Mexico

Abstract: Perennial cankers and consequent grapevine dieback are a major problem in vineyards of Sonora and Baja California, the most important grape-production areas of Mexico. In order to identify the canker-causing agents, symptomatic arms, cordons, and trunks were collected from 13 and 6 vineyards in Sonora and Baja California, respectively. Two Botryosphaeriaceae spp., Lasiodiplodia theobromae and Diplodia seriata, were isolated frequently from infected wood and identified based on morphological and cultural charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
103
2
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(129 citation statements)
references
References 24 publications
15
103
2
9
Order By: Relevance
“…The relatively common occurrence of L. theobromae in Cameroon, compared to the other regions sampled in this study, could also reflect a climatic influence. Lasiodiplodia theobromae appears to occur most commonly in consistently warm areas (Taylor et al 2005;Urbez-Torrez et al 2008) and the climatic conditions in the localities where samples were collected in this study apparently support the findings.…”
Section: Fig 9 Mean Cambial Lesion Lengths (Mm) For Each Botryosphasupporting
confidence: 81%
“…The relatively common occurrence of L. theobromae in Cameroon, compared to the other regions sampled in this study, could also reflect a climatic influence. Lasiodiplodia theobromae appears to occur most commonly in consistently warm areas (Taylor et al 2005;Urbez-Torrez et al 2008) and the climatic conditions in the localities where samples were collected in this study apparently support the findings.…”
Section: Fig 9 Mean Cambial Lesion Lengths (Mm) For Each Botryosphasupporting
confidence: 81%
“…rainfall, humidity and host stress. Climate is suggested as a limiting factor as different Botryosphaeriaceae species dominate the colonisation of grapevine in Mexico (Úrbez-Torres et al, 2008), Spain (Úrbez-Torres et al, 2006), South Australia and New South Wales (Pitt et al, 2010). Among the genera of Botryosphaeriaceae there does seem to be a general trend of Lasiodiplodia species being adapted to tropical to sub-tropical locations (Abdollahzadeh et al, 2010;Alves et al, 2008;Begoude et al, 2010;Burgess et al, 2006a;Pavlic et al, 2004) and Neofusicoccum species to Mediterranean and temperate locations Crous et al, 2007;Phillips et al, 2002;Slippers et al, 2004bSlippers et al, , 2004cTaylor et al, 2009;van Niekerk et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Species with a wide host range often also behave as latent pathogens (Slippers et al 2005a;Slippers et al 2005b) and ) with the ability to cause disease symptoms on hosts, as shown in pathogenicity trials (Fraser and Davison 1985;Shearer et al 1987) Smith et al 1994) and as disease records in the field (Barnard et al 1987;Fraser and Davison 1985;Shearer 1994;Úrbez-Torres et al 2008). Some of the Botryosphaeriaceae exhibit a very restricted host range such as D. santalui restricted to S. acuminatum, and D. moneti restricted to A. rostellifera and A. cochlearis (Taylor et al 2009).…”
Section: Discussionmentioning
confidence: 99%